Characteristics and Gas-Bearing Properties of Yanchang Formation Shale Reservoirs in the Southern Ordos Basin - Zhendong Gao; Yongdong Wang; Xiaoyu Gu; Hanlie Cheng; Nnamdi Puppe (Geofluids)
Ordos Basin is a multicycle superimposed cratonic basin in northern China with a simple internal structure and a gentle stratigraphic slope. It is characterized by extensive development, numerous oil and gas-bearing layers, and complete source-reservoir-caprock assemblages. However, the research on continental shale reservoirs and gas-bearing characteristics in the southern part of the basin is not in-depth enough, which restricts the further exploration and development of shale gas in this area. In this paper, the development characteristics of pores and fractures in shale reservoirs and the gas-bearing characteristics of Yanchang Formation shale in the study area are summarized by the comprehensive use of field outcrop, core, and logging, combined with common thin section observation, scanning electron microscope observation, X-ray diffraction analysis, and other methods and techniques. Research indicates that the cement content of the sandstone in the Yanchang Formation reservoir in the south of Ordos is generally 5%-25%. The reservoir also has a large number of primary pores, secondary pores, and microfractures. The gas content of the Yanchang Formation shale represented by Chang 7 is related to both organic matter and pore structure.